GAMBARAN STATUS GIZI DAN FUNGSI PARU PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK STABIL DI POLI PARU RSUD ARIFIN ACHMAD - Indra Yovi; Laode Burhanuddin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTChronic Obstructive Pulmonary Disease (COPD) is a disease that become the health problem in Indonesia and world until now. Nutritional status is a health condition as the result of interaction between food, body and environment. The main function of pulmo is gases transfer between atsmosphere and blood. The important relation between nutrition and pulmonary function can be seen from nutritional status. Nutritional status affected the quality of life COPD’s patient. This study was using descriptive methods with crossectional approached. The sampling technique used total sampling. The study was held on February – March 2015 with number of sample is 43 persons whom COPD stable patients in pulmonary polyclinic of Arifin Achmad general hospital. The result of this study is characteristic based on age showed 25 (28,1%) persons are > 65 years old, 38 (88,4%) persons are male. Characteristic based on occupation showed 24 (55,8%) persons were retired with the patient smoking status as the active smokers were 19 (44,2%) persons. COPD’s patient who had heavy degree of pulmonary function were 21 (48,8%) persons and 18 (41,9%) persons had normal nutritional status.Keywords:COPD patient, nutritional status, lung function